Six Floor And One Basement Hotel Design With The Intermediate Reinforced Concrete Moment Frames In Surakarta - Rabbani, Yusron Abdullatif, Yenny Nurchasanah, S.T., M.T, Budi Setiawan, S.T., M.T (2016)
In 2011, the Indonesian government set Wonderful Indonesia as the Indonesian tourism brand management. Based on data from 2014, the number of foreign tourists coming to Indonesia by 9.4 million, or grew by 7:05% compared to the previous year.The number of foreign tourists coming to Indonesia, urging local government to pay attention to supporting facilities to provide comfort to the tourists during the tour. one of the supporting facilities are hotel.Therefore, it will be planned a six floors and one basement with intermediate reinforced concrete moment frames in surakarta. Which should be considered in the plan for an building structure including safety aspects, architectural and economic.The hotel building planning refers to the Indonesian regulatory standards (SNI), hat is SNI-1726:2002 (Earthquake Resilience Planning Procedures for Building Structures and Non-Building) and SNI-2847:2013 (Requirements for Structural Concrete Building). The building plan includes the main structure (the structure of columns and beams under the structure) as well as a steel roof truss structure and a plate structure (slabs, stairs and basement). With the location of the building in Surakarta and the calculation of land sites including category classification SD (soil medium) and included into the earthquake zone 3, the obtained values of Ca and Cv seismic coefficient is 0.23 and 0.33.For planning needs of earthquake loads on buildings SRPMM.Ie buildings used primacy factor with a value of 1 (including residential buildings) response modification factor (R) 5.5, seismic load analysis method using Time History analysis using data akselerogram Earthquake El Centro N-S which had been recorded on May 15, 1940 in California. Quality of the concrete used fc '30 MPa, and the quality of threaded steel reinforcement fy 400 MPa and plain reinforcement fy 240 MPa. 300/500 dimensional beam structure is planned for the 1st floor to the roof. While for column with the dimensions 500/700 planned for the basement floor up to the 6th floor.Under the planned structure wearing pile foundation with specifications Prestressed Concrete Piles Spun Ex- WIKA Class-C diameter of 400 mm and Qijin material = 111.5 Ton, at a depth of 9m, with dimensions poer 1800x1800x650mm to 4 poles and poer 2000x2000x1050 mm to 4 poles. And the plan of slof dimensio is 300/500.